The Influence of Performance Feedback on Employee Performance Which is Mediated by Clarity of Performance Goals and Moderation of the Level of Autonomy in Employees in The Ministry of Transportation - Samudra Windo; Sugiyanto Sugiyanto (International Journal of Economics, Management and Accounting (IJEMA), 2024)
Performance feedback plays an important role in human resource strategies to improve employee performance through clarity of performance targets by providing good work facilities to motivate employees in carrying out activities. The aim of this research was to examine whether performance feedback would contribute to employee performance in the context of public organizations. This type of research is quantitative with a purposive sampling technique distributed through questionnaires to 110 service employee respondents within the Ministry of Transportation who are 20 years old and have worked for at least 2 years and reside in the Tangerang Regency area. Primary data analysis was carried out using the Structural Equation Modeling (SEM) method. The results of this research show that 4 of the 5 proposed hypotheses are accepted, and the work feedback variable has the greatest direct influence on the clarity of performance targets, then performance feedback has the greatest indirect influence on the relationship between clarity of work targets and employee performance. This research contributes to employees of the Ministry of Transportation in maintaining and improving employee performance by looking at several factors in the clarity of performance targets formed from performance feedback in an optimal and measurable manner. For further research, the researcher suggests that there is a need to develop variables so that other variables that are related to this research can also be used optimally.